Low-dimensional organic conductors - Graja, Andrzej (Singapore World Scientific, 1992)
This book is a review of physical properties of organic conductors and superconductors. It is amply illustrated and contains numerous data concerning the latest elements and equipment constructed of low-dimensional organic conductors.
Index: p.302-306
Keywords: Cơ bản